Die Fragmente : Der Brief an Julius von Rom - Marcellus, of Ankara, Bishop of Ankara, approximately 280-approximately 374. (Vigiliae Christianae, Supplements, 1997)
Marcellus of Ancyra (ca. 285/290 - circa 374) was one of the prominent bishops who fought against the Eusebians at the council of Nicaea. After this council, he was the first to attack them, and especially Asterius of Cappadocia. Only fragments of his work were preserved. These fragments, together with a letter which he wrote in 341 to Julius of Rome, the only undisputed works of Marcellus, are collected in this volume. The book opens with an introduction, contains the edition with German translation, notes and indices. In contrast to the former editions of Marcellus' works, this edition follows substantially the new order of the fragments established by K. Seibt (1994). As a result, Marcellus' fragments give an idea of how his work was originally structured.